Penerapan Metode EUCS dalam Evaluasi Sistem CSMS pada PT Jaya Abadi Kontrindo - Steven Tan; Dicky Pratama (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
This study aims to evaluate user satisfaction with the Customer Service Management System (CSMS) at PT Jaya Abadi Kontrindo using the End User Computing Satisfaction (EUCS) method. The CSMS is utilized to support various operational activities, such as purchase requests, payment requests, accounts receivable management, sales order rescheduling, and digital report generation. However, the system still faces several issues, including suboptimal response time, lack of user guidance, and the absence of a specific evaluation of user satisfaction. This study employs a qualitative approach by distributing questionnaires to 50 CSMS users using purposive sampling. The instrument was developed based on the five EUCS dimensions, namely content, accuracy, format, ease of use, and timeliness. The collected data were analyzed using validity testing, reliability testing, mean-based descriptive analysis, and Spearman correlation analysis. The results show that all questionnaire items are valid and reliable. In addition, all EUCS dimensions fall into the satisfied category, with the highest score in ease of use and the lowest in content. The Spearman correlation results also indicate that all EUCS dimensions have a significant relationship with user satisfaction.